Exploring the Influence of Teacher Qualifications, Classroom Size, Student Age, and Parental Involvement on High School Drop Out Rates in Sukabumi Regency - Dea Permatasari; Bhenu Artha (Jurnal Pendidikan West Science, 2023)
The purpose of this study was to explore the influence of teacher qualifications, classroom size, student age, and parental involvement on high school dropout rates in Sukabumi Regency. Using data from a survey of high school students in the region, multiple regression analysis was used to examine the relationships between these predictor variables and dropout rates. The results showed that all four predictor variables were significant predictors of dropout rates, with teacher qualifications and student age having the strongest influence. Specifically, having a teaching degree and license, having less than five years of teaching experience, being between the ages of 18 and 20, and larger class sizes were associated with higher dropout rates, while regular communication with teachers was associated with lower dropout rates. These findings suggest that efforts to improve teacher qualifications, reduce class sizes, and increase parental engagement and communication could help reduce high school dropout rates in Sukabumi Regency.